Synthesis of Two-Color Laser Pulses for the Harmonic Cutoff Extension - 王国利 周丽华 赵松峰 周效信 (Communications in theoretical physics, 2016)
Increasing simultaneously both the cutoff energy and efficiency is a big challenge to all applications of high-order harmonic generation（HHG）.For this purpose,the shaping of the waveform of driving pulse is an alternative approach.Here,we show that the harmonic cutoff can be extended by about two times without reducing harmonic yield after considering macroscopic propagation effects,by adopting a practical way to synthesize two-color fields with fixed energy.Our results,combined with the experimental techniques,show the great potential of HHG as a tabletop light source.